Risk management disclosure in islamic financial institutions in Malaysia: Pre and post financial crisis / Rosnadzirah Ismail … [et al.] - Ismail, Rosnadzirah; Abdul Rahman, Rashidah; Ahmad, Normah; Mokhtar, Siti Hilda (Research Management Institute (RMI), 2012)
The purpose of this study is to examine the risk management disclosure by all seventeen Islamic Financial Institutions (IFIs) in Malaysia from 2006 to 2009, covering the period before, during and after the global financial crisis. This study also aims to examine the relationship between corporate governance mechanisms on the level of risk management disclosure. A disclosure checklist consists of mandatory and voluntary items were developed to measure the level of risk disclosure. The descriptive result shows the risk management disclosure among the Islamic Financial Institutions was satisfactory. Analysis for the four-year period revealed that the risk disclosure has significantly improved before and after the financial crisis indicating that Islamic financial institutions have taken the necessary measures to improve their disclosure. Independent non-executive (BINE) and non-independent non-executive directors (BNINE) were found to have effect on the risk management disclosure indicating that external directors have significant influence on management.